A comparative study on the pharmacovigilance scoring of causality assessment grading and staging of topical pharmacotherapy of ofloxacin 0.3% ophthalmic solution in bacterial conjunctivitis and ofloxacin 0.3% otic solution in otitis externa - Hazra, Moumita (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Topical pharmacotherapeutic modalities would minimalize systemic adverse effects. Ofloxacin, the bactericidal racemic mixture, has inhibitory effects on DNA gyrase, DNA topoisomerase IV and IL-1α, IL-6, and IL-8. This was a comparative study for pharmacovigilance scoring of causality assessment grading and staging of topical ofloxacin pharmacotherapy in bacterial conjunctivitis and otitis externa. Methods: Group A=50 bacterial conjunctivitis patients were prescribed topical ophthalmic 0.3% ofloxacin, 2 drops in each eye after every 3 hours for 2 days, and 2 drops in each eye after every 6 hours for next 5 days; and group B=50 otitis externa patients were prescribed topical otic 0.3% ofloxacin, 3 drops in each ear after every 6 hours for first 2 days, and 5 drops in each ear after every 12 hours for next 5 days. Comparative adverse drug reactions occurrence, like transient ocular burning or discomfort, ocular irritation, redness, stinging, pruritis, photophobia, ocular watering and dryness in group A, and pruritis, headache, dizziness, mild ear pain, rashes, and hypersensitivity reactions in group B, were analysed with adverse event case report forms, on days 0, 3, 5, 7, 10, 15, 30, and on follow-ups, with causality assessment scores, from adverse drug reactions grading and staging. Results: The occurrence of adverse effects were statistically non-significant, in both groups, with causality assessment scoring for group A: -11, none on average=Unlikely causality, and group B: -11, none on average= Unlikely causality. Conclusions: Topical ofloxacin therapy in group A and group B patients, were safe and tolerable; with nil causality of association of adverse drug reactions.